2019
DOI: 10.1039/c8ra09853k
|View full text |Cite
|
Sign up to set email alerts
|

A green approach of preparation of fine active alumina with high specific surface area from sodium aluminate solution

Abstract: A green preparation of fine active alumina from saturated sodium aluminate solution by phase evolution is presented. High capillary pressure, numerous mesopores, and the inhibition of aggregation produced FAA with an extremely high specific surface area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…Recently, synthesis of ammonium aluminium carbonate hydroxide (AACH, NH 4 Al(OH) 2 CO 3 ) has become a promising alternative for preparation of nanostructured Al 2 O 3 . [1][2][3]9,14,[20][21][22][23] AACH is typically prepared by liquid-liquid precipitation using different aqueous aluminium solutions (NH 4 Al(SO 4 ) 2 , Al(NO 3 ) 3 , AlCl 3 , and NaAlO 2 ). 3,9,14,20 It has been shown that the choice of an appropriate precipitating agent is crucial for preparation of pure AACH.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…Recently, synthesis of ammonium aluminium carbonate hydroxide (AACH, NH 4 Al(OH) 2 CO 3 ) has become a promising alternative for preparation of nanostructured Al 2 O 3 . [1][2][3]9,14,[20][21][22][23] AACH is typically prepared by liquid-liquid precipitation using different aqueous aluminium solutions (NH 4 Al(SO 4 ) 2 , Al(NO 3 ) 3 , AlCl 3 , and NaAlO 2 ). 3,9,14,20 It has been shown that the choice of an appropriate precipitating agent is crucial for preparation of pure AACH.…”
mentioning
confidence: 99%
“…[1][2][3]9,14,[20][21][22][23] AACH is typically prepared by liquid-liquid precipitation using different aqueous aluminium solutions (NH 4 Al(SO 4 ) 2 , Al(NO 3 ) 3 , AlCl 3 , and NaAlO 2 ). 3,9,14,20 It has been shown that the choice of an appropriate precipitating agent is crucial for preparation of pure AACH. The product of precipitation using NH 4 HCO 3 is a mixture of boehmite (AlO(OH)) and AACH, 14,20 whereas using (NH 4 ) 2 CO 3 results in formation of only the AACH phase with low crystallinity.…”
mentioning
confidence: 99%
See 3 more Smart Citations